Fast Mapping in Healthy Young Adults: The Influence of Metamemory - Ramachandra, Vijayachandra; Rickenbach, Bryna; Ruda, Marissa; LeCureux, Bethanie; Pope, Moira (Journal of psycholinguistic research, 2010)
Several research studies suggest the significant role played by metamemory in lexical abilities of both adults and children. To our knowledge, there have been no studies to date that have explored the role of metamemory (Judgments of Learning) in fast mapping of novel words by adults. One hundred and twelve undergraduate students were given tasks of fast mapping and judgments of learning. A one-way Multivariate Analysis of Variance revealed that participants who performed well on fast mapping had superior global and item-by-item absolute prediction scores compared to poor performers. However, the good and poor performers did not significantly differ in their item-by-item relative predictive accuracy (Goodman–Kruskal gamma correlations) in the immediate as well as the delayed judgments of learning conditions. The possible reasons for inferior gamma correlations, the methodological issues for future research and the clinical implications for the assessment and treatment of adults with lexical deficits are discussed.